Colonial armies in Southeast Asia - HACK, Karl (Institutional Knowledge at Singapore Management University, 2005)
Colonial armies were the focal points for some of the most dramatic tensions inherent in Chinese, Japanese and Western clashes with Southeast Asia. The international team of scholars take the reader on a compelling exploration from Ming China to the present day, examining their conquests, management and decolonization. The journey covers perennial themes such as the recruitment, loyalty, and varied impact of foreign-dominated forces. But it also ventures into unchartered waters by highlighting Asian use of 'colonial' forces to dominate other Asians. This sends the reader back in time to the fifteenth century Chinese expansion into Yunnan and Vietnam, and forwards to regional tensions in present-day Indonesia, and post-colonial issues in Malaysia and Singapore. Drawing these strands together, the book shows how colonial armies must be located within wider patterns of demography, and within bigger systems of imperial security and power - American, British, Chinese, Dutch, French, Indonesian, and Japanese - which in turn helped to shape modern Southeast Asia. Colonial Armies in Southeast Asia will interest scholars working on low intensity conflict, on the interaction between armed forces and society, on comparative imperialism, and on Southeast Asia.